Electrochemical performance of activated carbon-supported vanadomolybdates electrodes for energy conversion. Issue 19 (1st October 2021) - Maity, Sukanya; Vannathan, Anjana Anandan; Kella, Tatinaidu; Shee, Debaprasad; Das, Partha Pratim; Mal, Sib Sankar
Abstract: Reinforcing polyoxomolybdates (POMs) into the activated carbon (AC) template engenders a nanohybrid electrode material for high-performance supercapacitor applications. Herein, a first-time novel integration of two polyoxometalates ([PVMo11 O40 ] 4-, [PV2 Mo10 O40 ] 5- ) with AC has been demonstrated, and their structural and electrochemical performances were analyzed. AC-VMo11 composite displayed an enhanced capacitance of 450 Fg -1 with an improved energy density of 59.7 Whkg -1 . Furthermore, the symmetric supercapacitor cell for AC-VMo11 and AC-V2 Mo10 showed high cell capacitances of 38.8 and 20.01 mF, respectively, alongside 99.99% capacitance retention of over 5000 cycles. In addition, the influence of ionic liquid as an electrolyte on AC-V2 Mo10 based supercapacitor cell was investigated in tetrabutylammonium bromide (TBAB) electrolyte solution.